De geparfumeerde tuin. - Santillo, Ellen; Vandromme, Jan; Sonnaert, Marc; Kunstencentrum België, Hasselt (Genk : Centrum Bruno Renson, 2005)
Hoeben, Marcel ; Holtappels, Jos ; Lipkens, Rene ; Motmans, Luk ; Oyen, Walter ; Santillo, Ellen ; Vandromme, Jan ; Vanheusden, Marie-Ange ; Vansummeren, Kristien ; et al.
Kunstencentrum België, Hasselt, 23 september - 8 oktober 2005
kunstcatalogus